Electrochemical Determination of Metronidazole in Tablet Samples Using Carbon Paste Electrode - Yosef Nikodimos; Meareg Amare (Journal of Analytical Methods in Chemistry)
Cyclic voltammetric investigation of metronidazole at carbon paste electrode revealed an irreversible reduction peak centered at about −0.4 V. Observed peak potential shift with pH in the range 2.0 to 8.5 indicated the involvement of protons during the reduction of metronidazole, whereas the peak potential shift with scan rate in the range 10–250 mV/s confirmed the irreversibility of the reduction reaction. A better correlation coefficient for the dependence of peak current on the scan rate than on the square root of scan rate indicated an adsorption controlled kinetics. Under the optimized method and solution parameters, an excellent linearity between the reductive peak current and the concentration of metronidazole was observed in the concentration range 1.0 × 10−6 to 5.0 × 10−4 M with a correlation coefficient, method detection limit (based on s=3σ), and limit of quantification of 0.999, 2.97 × 10−7 M and 9.91 × 10−7 M, respectively. Good recovery results for spiked metronidazole in tablet samples and selective determination of metronidazole in tablet formulations in the presence of selected potential interferents such as rabeprazole, omeprazole, and tinidazole confirmed the potential applicability of the developed method for the determination of metronidazole in real samples like pharmaceutical tablets.